Fetal TEI Index in Pregnancies with Intrahepatic Cholestasis of Pregnancy: A Case-Control Study - Guerra, Manuel; Haye, María Teresa; Montaño, Ignacio; Toro, Victoria; Maiz, Nerea (American Journal of Perinatology, 2025)
First, to explore differences in fetal cardiac function in patients with and without intrahepatic cholestasis of pregnancy (ICP) based on the TEI index. Second, to explore a potential correlation between TEI index and bile acid levels in pregnant women with ICP. Third, to study changes in the TEI index of fetuses from pregnant women with ICP after administration of ursodeoxycholic acid (UDCA).This is a prospective observational case-control study conducted at Hospital Clínico San José and Clínica RedSalud Vitacura, both in Santiago, Chile, between April 2018 and October 2020. ICP was defined as palmar-plantar pruritus of nocturnal predominance for more than 1 week associated with a total bile acid level above 10 μmol/L. Control cases were women with pregnancies scheduled for induction or elective cesarean section between 37 and 40 weeks of gestation according to current protocols. Differences in the TEI index between cases and controls were assessed by the Wilcoxon test. The correlation between the TEI index and bile acid levels was assessed by the Spearman correlation test. Changes in TEI index before and after administration of UDCA were analyzed by the paired samples Wilcoxon test.A total of 181 pregnant women were included in the study, 109 women with ICP and 72 controls. The median gestational age at inclusion was 35.9 weeks (interquartile range [IQR], 33.0–38.9). The median TEI index was 0.31 (IQR, 0.29–0.36); this was significantly longer in fetuses of women with ICP ([0.34, IQR, 0.30–0.38] vs. [0.30, IQR, 0.28–0.31], p < 0.001). There was a significant correlation between bile acid levels and TEI index (0.584, p < 0.001). In 21 fetuses, the TEI index was measured a second time, 2 weeks later, following UDCA administration. The median TEI index decreased significantly following UDCA administration (0.40 ms before treatment [IQR, 0.36–0.42] vs. 0.33 after treatment [IQR, 0.32–0.38], p = 0.001), p = 0.001).The TEI index is increased in fetuses of women with ICP. TEI index was significantly correlated with bile acid levels, and administration of UDCA significantly reduced the TEI index.
Keywords: TEI Index; intrahepatic cholestasis of pregnancy; bile acids; ursodeoxycholic acid; transaminitis